Culture Modulates the Neural Correlates Underlying Risky Exploration - Qu, Yang; Lin, Lynda C.; Telzer, Eva H. (Frontiers in Human Neuroscience, 2019)
Most research on cultural neuroscience focuses on one dimension of culture: group membership or individual orientation. However, it is especially important to examine the intersection between the two to better understand the acculturation process. To examine the role of culture in the neural correlates of risky exploration, the current study recruited 22 American and 24 Chinese international students. Participants reported on their independent self-construal, a measure defining the self in terms of emphasizing unique attributes, and underwent an fMRI scan while completing a risk-taking task. At the group level, American (vs. Chinese) participants showed greater risky exploration on the task. Moreover, while independent self-construal was not related to American individuals’ behavioral performance and neural correlates of risky exploration, Chinese participants who reported greater independent self-construal recruited greater activation in regions of the cognitive control system (e.g., dorsolateral prefrontal cortex) and affective system (e.g., anterior insula), which was related to greater risky exploration. Taken together, our findings suggest that culture as group membership and individual orientation may interact with each other and relate to neural systems underlying risky exploration. This study highlights the importance of studying the role of culture at both group and individual level, which is particularly important to understand individuals as they acculturate to a new environment.